Assessing the Career Conflict Options of Senior Secondary School Students of Ado-Odo Ota Local Government, Ogun State, Nigeria - Samuel Adebayo Idowu; Tolu Elizabeth Ifedayo; Elizabeth Oluwatoyin Idowu (Research in Social Sciences and Technology, 2020)
Career choice is one of the most important decisions that students make, and this decision will affect them throughout their lives. This study adopts a descriptive research survey method for assessing career conflict options of senior secondary school students in Ado-Odo Ota Local Government, Ogun State, Nigeria. The data contains questionnaires administered to 373 male and female secondary school students from three private schools and three public schools in the Ado-Odo Ota Local Government. The data obtained from the questionnaires were categorized into a Demographic Data Inventory, Career Choice Scale, and Support, Interference, and Lack of Engagement Scale. Demographic information was analyzed using descriptive statistics, and simple linear regression analysis was used to test the three hypotheses generated for the study at 0.05 alpha levels of significance. The findings suggest that parental formal education has a significant effect on the choice of careers of students, and that the profession of parents has a minor influence on the choice of careers of students. The results also indicate that the socio-economic status of parents does not affect the career choice of secondary school students. Based on the findings, this study recommends that parents be trained in career counseling to help parents direct their children in their career choices. Counseling units in the Ministry of Education should also coordinate orientation activities and provide information on the broad variety of career opportunities open to students. Finally, future research should be carried out on the contradictory effect of teachers and school counselors on the career choices of secondary school students.